HUBUNGAN USIA, KADAR KOLESTEROL, DAN BENIGN PROSTATIC HYPERPLASIA PADA USIA 31–80 TAHUN - Zayanda Fitri; Kurniasari Kurniasari (Jurnal Akta Trimedika, 2026)
Benign Prostatic Hyperplasia (BPH) is a disease that can affect men starting at age 30. In Indonesia, the incidence of this disease remains quite high. BPH impacts the quality of life of sufferers. Age and dyslipidemia are two factors that play a role in the occurrence of BPH. The purpose of this study was to analyze the relationship between age, total cholesterol, LDL cholesterol, HDL cholesterol, and the incidence of BPH. This study used a cross-sectional approach. A total of 68 male patients aged 31-80 who visited the Urology Polyclinic at a private hospital in West Jakarta between November and December 2023 were included in this study. Patients with prostate cancer or a family history of BPH were excluded from this study. Data on BPH diagnosis were collected from medical records, while total cholesterol, HDL cholesterol, and LDL cholesterol levels were measured using a cholesterol meter. All collected data were analyzed using the Chi-square test and Fisher's Exact test. The results of the analysis showed a relationship between age and the incidence of BPH (p=0.000), but a relationship between total cholesterol levels (p=0.415), LDL cholesterol levels (p=0.790), and HDL cholesterol (p=0.914) and the incidence of BPH was not found. The incidence of BPH is related to age, but cholesterol levels do not play a direct role in this incidence.